Natural dye plants used by Dayak Iban in Sungai Utik, Kapuas Hulu, West Kalimantan, Indonesia - Wahdina WAHDINA; Dede Setiadi; Yohanes Purwanto; Ibnul Qayim (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wahdina, Setiadi D, Purwanto Y, Qayim I. 2021. Natural dye plants used by Dayak Iban in Sungai Utik, Kapuas Hulu, West Kalimantan, Indonesia. Biodiversitas 22: 1397-1404.  Natural dye plants used by indigenous people in Indonesia are considered an important and unique gene pool, especially in Kalimantan (Indonesian Borneo), known to have high biodiversity and endemicity. Dayak Iban people in Sungai Utik, Kapuas Hulu District, West Kalimantan Province, Indonesia  are considered a culturally important group, recognized by their customary forest and harmonious living with nature. One of the traditional knowledge practiced by this group is the use of dye plants for along time to make traditional woven fabric and various plaiting handicrafts. This study aims to investigate the types of natural dye plants used by the Dayak Iban people in Sungai Utik, and how the local people use them traditionally. Information about the dye plants used and their utilization process was obtained through in-depth interview methods. We also identified the color produced by the dye plants. There were 15 plant species used as dye plants in Sungai Utik Village. The dye plants are used for plaiting and yarn dyeing as traditional woven material with white, red, and black colors are the only colors used. The most important dye plants are engkerebai kayoh (Psychotria malayana) for red dye color and rengat kikat (Clerodendrum laevifolium) for black dye color. The coloring process includes the yarn oiling, tying, measuring, dyeing, and drying, followed by weaving process. The people in Sungai Utik obtain the dye plants in their customary forest as they keep their forests as a highly valuable treasure.